Litopenaeus vannamei Shrimp Aquaculture Development Strategy in Patutrejo Village, Purworejo Regency, Central Java: Analisis Strategi Pengembangan Budidaya Udang Vaname di Desa Patutrejo, Kabupaten Purworejo - Pujiastuti, Hanan; Hardjanto, Arini (Indonesian Journal of Agricultural Resource and Environmental Economics, 2025)
Patutrejo Village, which is directly adjacent to the Indian Ocean in the south, is suitable for vaname shrimp aquaculture. However, in recent years, farmers began to face the problem of high-intensity harvest failure, resulting in a decline in the number of farmers in the location. The lack of information obtained by farmers regarding disease management and good cultivation techniques also exacerbates the condition of cultivation in the study location. The aims of this study are (1) to analyze the income of vaname shrimp farming, (2) to analyze the factors that influence farmers' decision to continue shrimp aquaculture, and (3) to develop a strategy for shrimp aquaculture development. The methods used to answer the research question are income analysis, logistic regression and an analytical hierarchy process. Income analysis with the assumption of average price and harvest volume in the first cycle of 2024 gives results that the R/C ratio is more than one, so vaname shrimp farming in Patutrejo Village is profitable. Binary logistic regression analysis revealed that land area and farmer income were the main factors influencing farming decisions to continue shrimp aquaculture. Reducing the number of harvest failures could increase farmers' income and farming interest. In the preparation of aquaculture development strategies based on the RPJMN and Purworejo District Strategic Plan, the Analytical Hierarchy Process (AHP) recommends training in good fish farming and dissemination of information on shrimp disease management. Desa Patutrejo merupakan desa yang berbatasan langsung dengan Samudra Hindia di bagian selatan sehingga mendukung kegiatan budidaya tambak udang vaname. Namun beberapa tahun terakhir, petambak mulai menghadapi kendala tingginya intensitas gagal panen sehingga jumlah petambak di lokasi menurun. Minimnya informasi yang didapatkan petambak mengenai penanganan penyakit dan teknik budidaya yang baik juga memperparah kondisi budidaya di lokasi penelitian. Berdasarkan hal tersebut tujuan dari penelitian ini yaitu (1) menganalisis pendapatan budidaya udang vaname, (2) menganalisis faktor-faktor yang memengaruhi keputusan petambak untuk melanjutkan budidaya, (3) menyusun strategi pengembangan budidaya. Metode penelitian yang digunakan adalah analisis pendapatan, regresi logistik dan anaylthical hierarchy process. Analisis pendapatan dengan asumsi harga yang digunakan adalah harga dan volume rata-rata pada siklus pertama 2024 didapatkan hasil bahwa R/C rasio lebih dari satu, sehingga budidaya udang vaname di Desa Patutrejo masih menguntungkan. Analisis regresi logistik biner mengungkap bahwa luas lahan dan pendapatan petambak menjadi faktor utama yang memengaruhi keputusan petambak dalam menlanjutkan budidaya udang vaname. Upaya untuk meningkatkan pendapatan dan minat petambak berbudidaya dapat dilakukan dengan menurunkan angka gagal panen. Strategi untuk mencapai tujuan tersebut dilakukan dengan pelatihan budidaya ikan yang baik dan penyebaran informasi penanganan penyakit udang.